Evolution of Libraries in the Digital Era: Redefining Access, Education, and Cultural Preservation - Rahmanova, Ayten (İstanbul Medeniyet Üniversitesi, 2025)
The digital revolution has significantly reshaped libraries, transforming them from traditional repositories into dynamic, technology-driven centres of information, education, and cultural preservation. This study investigates the comprehensive digital transformation of libraries, with a focus on the integration of electronic resources, virtual reality (VR), augmented reality(AR), digital catalogues, multimedia labs, and maker spaces. Utilizing a multi-method approach, the research analyzes statistical data on user engagement, revealing a consistent 20% annual increase in users accessing e-books and journals globally since 2010. Additionally, surveys conducted among students and researchers in Azerbaijan indicate a 25% rise in electronic resource usage since 2015, with modern search tools enhancing information retrieval speed by 30%. The incorporation of VR and AR technologies is explored for their potential to enrich educational experiences and preserve cultural heritage. At the same time, multimedia labs and maker spaces are examined for their roles in fostering innovation and skill development. Despite these advancements, libraries face significant challenges such as the digital divide, information overload, privacy concerns, data security, and ensuring accessibility for all users. Libraries have started to address these challenges through continuous adaptation, investing in cutting-edge technologies, and developing digital literacy programs to bridge the digital divide, manage information effectively, and protect user privacy. The findings highlight the critical role of libraries in the digital age, underscoring their evolution into inclusive, technologically advanced institutions that support education, research, and cultural enrichment. The study underscores the importance of sustained investment in digital infrastructures to maintain libraries' pivotal role in modern society.